EFFECT OF 5E LEARNING MODEL ENRICHED WITH ANALOGIES ON ACADEMIC ACHIEVEMENT OF STUDENTS - Hacı Mehmet ÇOBAN (Fırat University, 2020)
One of the most important issues facing science teachers is to become capable of teaching more effectively. However, science teachers often tend to use only textbooks belong to science courses and think there is no need to use extra instructional sources. Hence, it is getting more vital for teachers to develop more constructive learning activities and persist on doing science consistently in the courses. The aim of this study is to determine the effect of analogue-enriched 5E learning model on the academic achievement of seventh grade students in the electrical energy unit. In the research, pre-test and post-test control group quasi-experimental design was used. The study group of the research consists of 58 middle school 7th grade students, 29 of whom are experimental and 29 of which are control groups, who are studying in a public school in Adıyaman in the summer term of 2015-2016 academic year. The intervention lasted for five weeks. The applications were carried out with 5E learning model in the control group and the 5E learning model enriched with analogies in the experimental group. Electrical Energy Achievement Test (EEBT) Görüşme and “Student Interview Form” were used to collect data. Data obtained from EEBT were analyzed statistically using SPSS package program; The answers given to the questions in the student interview form were analyzed using descriptive statistical method. The results of the analysis showed that the students in the experimental group differed significantly from the students in the control group in favor of the experimental group. The result of the study revealed that analogy-based 5E model was effective on students’ academic achievement in the unit of electricity.